Protocells: Rapid Growth and Fusion of Protocells in Surface‐Adhered Membrane Networks (Small 38/2020). Issue 38 (24th September 2020) - Köksal, Elif S.; Liese, Susanne; Xue, Lin; Ryskulov, Ruslan; Viitala, Lauri; Carlson, Andreas; Gözen, Irep
Abstract : In article number 2002529, Irep Gozen and co‐workers present experimental evidence that nucleation and growth of protocell‐like membrane compartments from surface‐adhered lipid nanotube networks are significantly enhanced at temperatures between 40 and 70 °C, and fusion can be initiated at ≈90 °C. They show that the microcontainers (5–15 μm) formed in this manner encapsulate and redistribute RNA, and corroborate that lipid nanotube–interconnected neighboring vesicles join and fuse more rapidly than in bulk suspensions.